Metagenomics: tools and techniques for data analysis - P.PANCHAL; P.CHUNARKAR-PATIL (International Journal of Pharma and Bio Sciences, 2017)
It is estimated that 99% of the microorganisms in nature are unculturable; it means scientist are dealing with only 1% of the microorganisms. These microbes cannot be culture in laboratory. Metagenomics is the solution to this problem which is culture independent cloning of the microorganisms. Metagenomics is the analysis of unculturable microbial genome which is extracted directly from environmental sample like water, soil, grassland etc. Recent advances in the technologies like Automated sequencing technologies, new binning algorithms and different statistical packages have advances the field of Metagenomics. The review summarizes the steps involved in metagenomics data analysis and various tools available for doing it. Based on this review, the researchers will get an idea about the appropriate tools and its utilization in data analysis.